Tourist route choice behavior and the walkability of historic areas in Kuala Lumpur City Center - Mollazadeh, Zeinab (2016)
In Asian cities, ability to walk (walkability) has depreciated because of a sharp increase in usage of the motorized vehicle. These days in urban design studies, walking and walkability interweaved with debates on the quality of urban spaces, urban life and urban tourism. In cities with a high level of walkability, individuals could reach their destination easily, while they could enjoy their walking experience. Following that, urban tourism offered one of the prominent concerns of urban design in recent decade. For visitors to experience a city, walkability could act as a catalyst, which provides them with a better image of the city. In the context of Kuala Lumpur as a premier city of Malaysia, it is crucial to make improvement in the condition of the city to create ''A World-Class City''. Regard to Kuala Lumpur Structure Plan 2020, it is a necessity to investigate the quality of tourists’ activities at the micro-level that covers the state of pedestrian experience, which is affected by quality of visual and configurational elements in the tourist places. It is demanding to concern about walkability issues to create a more conductive environment to movement pattern, purposes and needs of visitors. In this regard, to ameliorate the condition of existing route, there is a need to determine visual and configurational attributes of the route and pedestrian movement pattern, along with visitors' preference for choosing a particular route. Investigation on the effect of route attributes on route choice of pedestrian will illuminate how to provide visitors with walkable routes. The goal of this study is to improve the walkability of tourist areas in the city center of Kuala Lumpur through identification of route choice behavior of visitors. Following aspects were considered as major concerns of the research to answer the research question: Spatial movement of the visitors, visitors’ preferences, visual and configurational attributes of the routes. Totally 330 valid questionnaires gathered which determined tourist preferences and their spatial movement, along with their socio-demographic and trip characteristic. Through usage of audit instrument on urban design quality, visual attributes of the routes were measured, while configurational attributes of the route measured through Space Syntax. Findings of the study suggested that while both visual attribute (imageability and transparency) and configurational attributes (local integration) were influential attributes for choosing a route; for repeated visitors, the effectiveness of the local integration was increased. It is expected that findings of the study pioneer urban designers with an evidence-based method for better planning and designing of pedestrian routes, which cater for needs and experience of visitors to improve the walkability of tourist places.